2010
DOI: 10.1111/j.1365-2230.2010.03920.x
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant facial pemphigus vulgaris: correlation of skin lesions with the ratio of antidesmoglein antibodies 1 and 3

Abstract: Pemphigus vulgaris (PV) is an autoimmune bullous disease characterized by autoantibodies against desmogleins. We report a case of recalcitrant PV, which progressed from the mucosal to the mucocutaneous type, with a corresponding increase in anti-desmoglein (Dsg)1 and decrease in anti-Dsg3 antibody titres. Thus, the clinical features seemed to correlate with the ratio of anti-Dsg1 and 3. The patient also had anti-Dsg4 antibodies, which might be related to the nonscarring diffuse hair loss and marked facial invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“… 2 , 13 , 14 , 15 This may be because of higher levels of pemphigus antigens such as Dsg1 in the scalp. 9 , 16 , 17 , 18 , 19 Interestingly, in our study, Dsg1 ratios ( P < .001) were an independent predictor of hair loss in patients with PV. The role of Dsg1 antibodies in nonscarring alopecia is alluded to in the literature.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“… 2 , 13 , 14 , 15 This may be because of higher levels of pemphigus antigens such as Dsg1 in the scalp. 9 , 16 , 17 , 18 , 19 Interestingly, in our study, Dsg1 ratios ( P < .001) were an independent predictor of hair loss in patients with PV. The role of Dsg1 antibodies in nonscarring alopecia is alluded to in the literature.…”
Section: Discussionsupporting
confidence: 44%
“…Similarly, in an earlier study, an initial high anti-Dsg3 to anti-Dsg1 ratio was observed in a patient with PV, which was associated with diffuse nonscarring alopecia as this ratio decreased. 19 …”
Section: Discussionmentioning
confidence: 99%